Molecular characterization and morphological clustering of exotic early maturing rice (Oryza sativa L.) lines (Journal of the Bangladesh Agricultural University, 2014)
Characterization and variability analysis is important for the improvement of crop plant. This study aimed to evaluate the morphological and molecular variation of exotic early maturing rice (Oryza sativa L.) lines. A total of 32 exotic rice lines collected from different locations were genotyped and clustered using selected SSR markers. Based on morphological dendrogram, the lines were grouped into three clusters viz.I, II and III. Cluster I, cluster II and cluster III had 12, 11, 9 lines respectively. The results showed that the varieties were closely related belonging to the same cluster. DNA Markers namely Simple Sequence Repeats (SSR) is a useful tool for assessing genetic variations and resolving cultivar identities. Positive correlations were found between gene diversity, number of allele, the allele size range and the maximum number of repeats. Among the primers used RM147 identified more number of alleles and average PIC was 0.88. The UPGMA dendrogram based on Neis (1972) genetic distance grouped the 32 rice lines into three major clusters. This result indicates that the line which formed grouped together, they are less diverse. A significant level of polymorphism based on morphological and molecular levels was observed. Being grouped into three clusters C1-4-11-7P-2P-1P and IR 79201-49-1-1-1 could be utilized as potential parents for the improvement of yield in early maturing rice lines. DOI: http://dx.doi.org/10.3329/jbau.v11i2.19900 J. Bangladesh Agril. Univ. 11(2): 233-240, 2013